Phosphorylation of the conserved C‐terminal domain of ribosomal P‐proteins impairs the mode of interaction with plant toxins - Horbowicz‐Drożdżal, Patrycja; Kamel, Karol; Kmiecik, Sebastian; Borkiewicz, Lidia; Tumer, Nilgun E.; Shaw, Pang‐Chui; Tchórzewski, Marek; Grela, Przemysław (FEBS letters, 2021)
The ribosome is subjected to post‐translational modifications, including phosphorylation, that affect its biological activity. Among ribosomal elements, the P‐proteins undergo phosphorylation within the C terminus, the element which interacts with trGTPases or ribosome‐inactivating proteins (RIPs); however, the role of phosphorylation has never been elucidated. Here, we probed the function of phosphorylation on the interaction of P‐proteins with RIPs using the ribosomal P1‐P2 dimer. We determined the kinetic parameters of the interaction with the toxins using biolayer interferometry and microscale thermophoresis. The results present the first mechanistic insight into the function of P‐protein phosphorylation, showing that introduction of a negative charge into the C terminus of P1‐P2 proteins promotes α‐helix formation and decreases the affinity of the P‐proteins for the RIPs.